A kind of silk fibroin composite piezoelectric film and preparation method thereof

By introducing a glycine-chitosan composite solution in the preparation process of the silk fibroin film, the crystallization of silk fibroin in the direction of the β structure is solved, and the problem of insufficient piezoelectricity of silk fibroin films in the prior art is achieved, and the Silk fibroin composite film is taken into account in both piezoelectric coefficient, tensile strength and toughness, and is suitable for the application of flexible electronic devices.

CN115975230BActive Publication Date: 2025-04-29TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310063318.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2025-04-29
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

The prior art is difficult to improve its piezoelectric properties while maintaining the toughness and tensile strength of the silk fibroin film. Especially in the application of flexible electronic devices, the value of the piezoelectric constant d33 is low and it is difficult to meet actual needs.

Method used

By dissolving the glycine powder in chitosan acetic acid solution, a glycine-chitosan composite solution is formed, and mixed with the silk fibroin solution, a spin coating method is used to prepare a silk fibroin composite film, inducing the silk fibroin crystallization to form a film in the direction of the β structure, and improving piezoelectricity.

Benefits of technology

It achieves excellent performance of silk fibroin composite film in piezoelectric coefficient, tensile strength and toughness, meets the actual needs of flexible electronic devices, and simplifies process steps, reduces preparation costs and time, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115975230B_ABST
    Figure CN115975230B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method of a silk fibroin composite piezoelectric film, including dissolving glycine powder in a chitosan acetic acid solution to obtain a glycine-chitosan composite solution; dissolving the silk fibroin powder in a formic acid-calcium chloride solution to obtain a silk fibroin solution having a silk fibroin mass fraction of 10%; mixing the glycine-chitosan composite solution and the silk fibroin solution in a mass ratio of 0.1 to 0.5:1 to obtain a film-making solution; spin coating the film-making solution on a substrate, drying the film-making solution spin-coated on the substrate, and obtaining a silk fibroin composite film. The method is simple and easy to operate, and is suitable for large-scale manufacturing of a silk fibroin composite piezoelectric film. It also relates to a silk fibroin composite piezoelectric film prepared by the method, which has superior piezoelectricity and mechanical strength at the same time, and meets the practical application requirements of flexible electronic devices, especially flexible piezoelectric elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible electronic materials, and in particular to a silk fibroin composite piezoelectric film and a preparation method thereof. Background Art

[0002] Flexible electronic devices have broad application prospects in the fields of information, medical treatment, national defense, energy, etc., such as being prepared into flexible sensors, flexible batteries, flexible displays, electronic skin, flexible integrated microsystems, etc. Generally speaking, flexible electronic devices are realized by preparing functional components made of organic / inorganic materials on flexible substrates, so that the devices have excellent bendability, stretchability and adaptability while ensuring normal working conditions. Polytetrafluoroethylene, polydimethylsiloxane (PDMS), polyimide, fluorinated ethylene propylene and silicone rubber are widely used as flexible substrate materials for flexible electronic devices due to their mechanical properties in bending and stretching. However, it is difficult for these materials to achieve the biocompatibility and biodegradability required, especially in the medical field. In addition, most of these materials are expensive, which hinders the large-scale application of flexible electronic devices.

[0003] Silk fibroin is a natural silk fiber extracted from the products of insects such as silkworms and spiders. Researchers have found that silk fibroin, as a natural flexible material, has excellent biocompatibility and water solubility. By improving the preparation method or implementing post-processing, its biodegradability can vary from a few hours to a few years. At the same time, silk fibroin itself has high tensile strength and transparency, which is particularly important for the preparation of flexible electronic devices. In addition, silk fibroin has a low cost of acquisition and has a great advantage in economic benefits. Therefore, silk fibroin has great application potential in the preparation of flexible electronic devices.

[0004] At present, one of the main reasons that restricts the preparation of flexible electronic devices, especially piezoelectric films, from natural silk fibroin is that the piezoelectric constant d33 value is low, which is difficult to meet the needs of practical applications. Studies have found that the piezoelectricity of silk fibroin is proportional to the number of its β structures. To this end, the existing technology mainly increases the number of β structures in silk fibroin by immersion in alcohol solution or stretching treatment. In addition, when preparing silk fibroin films, the piezoelectric effect can also be increased by a long-term repolarization process under high pressure. However, these treatments affect the toughness and mechanical strength of silk fibroin films to varying degrees. Some studies have proposed that calcium chloride can be introduced during the preparation process to improve the toughness and tensile strength of silk fibroin films, but this also increases the α-helical structure and irregular curling structure in the secondary structure of silk fibroin, that is, reduces the number of β structures. Therefore, how to take into account the toughness, tensile strength and piezoelectricity of silk fibroin films has become a technical problem that needs to be solved in this field. Summary of the invention

[0005] In view of this, on the one hand, the present invention provides a method for preparing a silk fibroin composite piezoelectric film. The method has simple process steps and is easy to operate, and is suitable for large-scale production of silk fibroin composite piezoelectric films. At the same time, the silk fibroin composite piezoelectric film prepared by this method has excellent performance in various aspects, especially meeting the practical application needs of flexible electronic devices, especially flexible piezoelectric elements.

[0006] The preparation method of the silk fibroin composite piezoelectric film of the present invention comprises the following steps: dissolving glycine powder in a chitosan acetic acid solution to obtain a glycine-chitosan composite solution, wherein the chitosan mass fraction in the chitosan acetic acid solution is 1.5%, and the mass ratio of glycine to chitosan in the glycine-chitosan composite solution is 0.01-5:1; dissolving silk fibroin powder in a formic acid-calcium chloride solution to obtain a silk fibroin solution with a silk fibroin mass fraction of 10%; uniformly mixing the glycine-chitosan composite solution and the silk fibroin solution at a mass ratio of 0.1-0.5:1 to obtain a film-forming solution; spin coating the film-forming solution on a substrate, and drying the film-forming solution spin coated on the substrate to obtain a silk fibroin composite film.

[0007] In this way, the biomaterial glycine-chitosan solution is innovatively introduced into the preparation process of the silk fibroin composite film, so as to induce the silk fibroin to crystallize into a film in the direction of the β structure during the mixed spin coating process, without the need for additional alcohol solution immersion or stretching operations, and without the need to repolarize the film under high pressure, which simplifies the process steps, saves preparation costs and preparation time, and is conducive to large-scale production. In addition, the preparation process of the present invention retains the use of calcium chloride, thereby maintaining the strengthening effect of calcium chloride on the tensile strength and toughness of the silk fibroin film. At the same time, due to the large amount of β structure of silk fibroin induced by the glycine-chitosan solution, the piezoelectric coefficient of the silk fibroin composite film is not only not negatively affected by calcium chloride, but also further improved, so that the silk fibroin composite film prepared by the preparation method of the present invention has excellent performance in piezoelectric coefficient, tensile strength and toughness, which meets the actual needs of flexible electronic devices.

[0008] In an exemplary preparation method embodiment of the present invention, the chitosan acetic acid solution is prepared by dissolving chitosan powder in 1 v / v% acetic acid solution.

[0009] In this way, the chitosan powder can maintain its structure without degradation in a weak acid environment, and can be hydrolyzed under acid catalysis, so that the chitosan powder is fully dissolved in the solution.

[0010] In an exemplary preparation method embodiment of the present invention, after dissolving the glycine powder in the chitosan acetic acid solution, the method further comprises vigorously stirring the glycine-chitosan composite solution at room temperature for more than 0.5 hour.

[0011] In this way, the glycine powder can be fully dissolved in the chitosan solution, and the solution is more uniform.

[0012] In an exemplary preparation method embodiment of the present invention, the mass ratio of glycine to chitosan in the glycine-chitosan composite solution is 0.8:1.

[0013] In this way, at this ratio, chitosan further promotes the formation of glycine β structure, thereby more effectively inducing silk fibroin to form β structure in the subsequent steps. At the same time, the glycine-chitosan composite solution at this ratio does not affect the flexibility of the overall film.

[0014] In an exemplary preparation method embodiment of the present invention, the mass fraction of formic acid in the formic acid-calcium chloride solution is 70-99%, and the mass fraction of calcium chloride is 1-30%.

[0015] In this way, the dissolution efficiency of the lyophilized silk fibroin powder in the dissolution system can be promoted, making the silk fibroin dissolve more fully. In addition, at such a mass fraction, the introduction of calcium chloride further improves the tensile strength and toughness of the prepared silk fibroin composite piezoelectric film without causing a significant negative impact on its piezoelectric constant.

[0016] In an exemplary preparation method embodiment of the present invention, the mass ratio of the glycine-chitosan composite solution to the silk fibroin solution is 0.2: 1. In some places herein, this mass ratio is also referred to as the film-forming solution mixing ratio.

[0017] In this way, the β structure contained in the prepared silk fibroin composite piezoelectric film can be further improved, thereby further improving its piezoelectric constant.

[0018] In an exemplary preparation method embodiment of the present invention, the material of the substrate is selected from glass or polyethylene terephthalate.

[0019] In this way, the silk fibroin composite piezoelectric film is allowed to be easily peeled off from the substrate without damaging the integrity and surface flatness of the silk fibroin composite piezoelectric film, thereby allowing the prepared silk fibroin composite piezoelectric film to adhere to certain specific substrates for use in different use environments. In other words, in actual production, the silk fibroin conforming piezoelectric film can be manufactured by one entity, and the flexible electronic device or other electronic device containing the silk fibroin conforming piezoelectric film can be manufactured by another entity. It can be understood that, under the premise that the preparation method of the present invention does not damage any properties of the substrate, the silk fibroin conforming piezoelectric film can be directly prepared by the preparation method of the present invention on a specific substrate, eliminating intermediate steps such as peeling, storage and transportation. In other words, the silk fibroin conforming piezoelectric film and the flexible electronic device or other electronic device containing the silk fibroin conforming piezoelectric film can be manufactured by the same entity.

[0020] In an exemplary preparation method embodiment of the present invention, the rotation speed of the spin coating is 1 to 1000 rpm, and the duration of the spin coating is 12000 seconds.

[0021] In this way, the generation of the β structure of silk fibroin can be further promoted, and the surface flatness of the silk fibroin composite piezoelectric film can be improved. In addition, different film thicknesses can be achieved by adjusting the rotation speed and spin coating time to meet the requirements of different electronic components.

[0022] In an exemplary preparation method embodiment of the present invention, the drying temperature is 25 to 60° C., and the drying duration is 60 minutes or less.

[0023] In this way, the film-forming time of the film-forming solution can be shortened without producing a significant negative effect on the film-forming quality, thereby achieving rapid production and use.

[0024] One aspect of the present invention provides a silk fibroin composite piezoelectric film, which is prepared by any one of the above-mentioned preparation methods.

[0025] In this way, the piezoelectric coefficient of the silk fibroin composite piezoelectric film of the present invention exceeds that of most natural biological materials, while having excellent tensile strength and toughness. In addition, the surface of the silk fibroin composite piezoelectric film of the present invention is relatively smooth and can be adhered to various common substrates for applications in different fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The various technical features of the present invention and the relationship between them are further explained below with reference to the accompanying drawings. The accompanying drawings are exemplary, and some technical features are not shown in actual proportion. In addition, some drawings may omit technical features that are commonly used in the technical field to which the present invention belongs and are not essential for understanding and implementing the present invention, or additionally show technical features that are not essential for understanding and implementing the present invention. In other words, the combination of the various technical features shown in the accompanying drawings is not used to limit the present invention. In addition, in the full text of the present invention, the same figure numerals refer to the same content. The specific description of the drawings is as follows:

[0027] Figure 1 It is a schematic diagram of the structure of the silk fibroin composite film prepared by the preparation method of the present invention.

[0028] Figure 2 It is the FT-IR spectrum of the silk fibroin composite piezoelectric film prepared according to a comparative example and an embodiment of the present invention. DETAILED DESCRIPTION

[0029] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0030] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. If there is any inconsistency, the meaning described in the present invention or the meaning derived from the content recorded in the present invention shall prevail. In addition, the terms used in this description are only for the purpose of describing the embodiments of the present invention and are not intended to limit the present invention.

[0031] The term "comprising" used throughout the present invention should not be interpreted as being limited to the contents listed thereafter; it does not exclude other structural elements or steps. Therefore, it should be interpreted as specifying the existence of the technical features, integral bodies, steps or components mentioned, but does not exclude the existence or addition of one or more other technical features, integral bodies, steps or components and groups thereof.

[0032] Figure 1 Schematic diagram of the structure of the silk fibroin composite film prepared by the preparation method of the present invention, wherein the dark filaments represent the silk fibroin polymer, the light filaments represent the glycine-chitosan polymer, and the squares on the dark filaments represent the β structure of the silk fibroin. The specific chemical structure of the β structure is shown in Figure 1 For clarity, Figure 1 The other components of the silk fibroin composite film were omitted. Figure 1It can be intuitively understood that during the mixing, spin coating and drying process, the glycine-chitosan polymer and the silk fibroin polymer contained in the film-making solution of the present invention are intertwined, and the α and random curl structures of the silk fibroin polymer are induced by the nearby glycine-chitosan polymer to transform into a β structure, so that these silk fibroin polymers are crystallized into a film in a β structure. In this way, the preparation method of the present invention significantly increases the β structure of the silk fibroin composite film, thereby significantly improving the longitudinal piezoelectric coefficient of the silk fibroin composite piezoelectric film.

[0033] Some embodiments of the present invention are listed below.

[0034] Example 1

[0035] Step a1: Mix 1 ml of glacial acetic acid and 99 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 1 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 1 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 1.2 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 0.8:1.

[0036] Step b1: dissolving the freeze-dried silk fibroin powder into a formic acid-calcium chloride dissolution system with a mass fraction ratio of 95:5 to obtain a silk fibroin solution with a mass fraction of 10%.

[0037] Step c1: The glycine-chitosan composite solution obtained in step a1 and the silk fibroin solution obtained in step b1 are uniformly mixed at a mass ratio of 0.2:1 to obtain a membrane-forming solution.

[0038] Step d1: Spin-coat the film-forming solution prepared in c1 on a glass substrate at a rotation speed of 500 rpm for 30 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 60° C. for 20 minutes to obtain a silk fibroin composite film m1.

[0039] Example 2

[0040] Step a2: Mix 1 ml of glacial acetic acid and 99 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 1 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 1 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 6 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 4:1.

[0041] Step b2: dissolving the freeze-dried silk fibroin powder into a formic acid-calcium chloride dissolution system with a mass fraction ratio of 80:20 to obtain a silk fibroin solution with a mass fraction of 10%.

[0042] Step c2: The glycine-chitosan composite solution obtained in step a2 and the silk fibroin solution obtained in step b2 are uniformly mixed at a mass ratio of 0.1:1 to obtain a membrane-forming solution.

[0043] Step d2: Spin-coat the film-forming solution prepared in c2 on a glass substrate at a rotation speed of 700 rpm for 45 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 45° C. for 50 minutes to obtain a silk fibroin composite film m2.

[0044] Example 3

[0045] Step a3: Mix 2 ml of glacial acetic acid and 98 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 2 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 2 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 1.2 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 0.8:1.

[0046] Step b3: dissolving the freeze-dried silk fibroin powder into a formic acid-calcium chloride dissolution system with a mass fraction ratio of 70:30 to obtain a silk fibroin solution with a mass fraction of 10%.

[0047] Step c3: The glycine-chitosan composite solution obtained in step a3 and the silk fibroin solution obtained in step b3 are uniformly mixed at a mass ratio of 0.3:1 to obtain a membrane-forming solution.

[0048] Step d4: Spin-coat the film-forming solution prepared in c3 on a glass substrate at a rotation speed of 500 rpm for 30 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 60° C. for 30 minutes to obtain a silk fibroin composite film m3.

[0049] Example 4

[0050] Step a4: Mix 1 ml of glacial acetic acid and 99 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 1 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 1 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 1.2 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 0.8:1.

[0051] Step b4: dissolving the freeze-dried silk fibroin powder into a formic acid-calcium chloride dissolution system with a mass fraction ratio of 95:5 to obtain a silk fibroin solution with a mass fraction of 10%.

[0052] Step c4: the glycine-chitosan composite solution obtained in step a4 and the silk fibroin solution obtained in step b4 are uniformly mixed at a mass ratio of 0.5:1 to obtain a membrane-forming solution.

[0053] Step d4: Spin-coat the film-forming solution prepared in c4 on a glass substrate at a rotation speed of 500 rpm for 30 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 60° C. for 20 minutes to obtain a silk fibroin composite film m4.

[0054] Example 5

[0055] Step a5: Mix 2 ml of glacial acetic acid and 98 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 2 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 2 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 1.2 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 0.8:1.

[0056] Step b5: dissolving the freeze-dried silk fibroin powder into a formic acid-calcium chloride dissolution system with a mass fraction ratio of 70:30 to obtain a silk fibroin solution with a mass fraction of 10%.

[0057] Step c5: The glycine-chitosan composite solution obtained in step a5 and the silk fibroin solution obtained in step b5 are uniformly mixed at a mass ratio of 0.2:1 to obtain a membrane-forming solution.

[0058] Step d5: Spin-coat the film-forming solution prepared in c5 on a glass substrate at a rotation speed of 500 rpm for 30 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 60° C. for 30 minutes to obtain a silk fibroin composite film m5.

[0059] Comparative Example 1

[0060] The freeze-dried silk fibroin powder was dissolved in a formic acid-calcium chloride dissolution system with a mass fraction ratio of 95:5 to obtain a silk fibroin solution with a mass fraction of 10%. The silk fibroin solution was spin-coated on a glass substrate at a speed of 500 rpm for 30 seconds, and then the film-forming solution spin-coated on the glass substrate was dried at 60° C. for 20 minutes to obtain a silk fibroin film mx1.

[0061] Comparative Example 2

[0062] Step ax1: Mix 1 ml of glacial acetic acid and 99 ml of deionized water, and stir vigorously at room temperature for 1 hour to obtain a 1 v / v% acetic acid solution. Add 1.5 g of chitosan powder to 98.5 g of 1 v / v% acetic acid solution, and stir until the chitosan powder is completely dissolved to obtain a 1.5 wt% chitosan acetic acid solution. Dissolve 1.2 g of glycine powder in the 1.5 wt% chitosan solution, and then stir vigorously at room temperature for 2 hours to obtain a glycine-chitosan composite solution, in which the mass ratio of glycine to chitosan is 0.8:1.

[0063] Step bx1: dissolving the freeze-dried silk fibroin powder into XX (without calcium chloride) dissolution system to obtain a silk fibroin solution with a mass fraction of 10%.

[0064] Step cx1: the glycine-chitosan composite solution obtained in step ax1 and the silk fibroin solution obtained in step bx1 are uniformly mixed at a mass ratio of 0.2:1 to obtain a membrane-forming solution.

[0065] Step dx1: spin-coat the film-forming solution prepared in cx1 on a glass substrate at a rotation speed of 500 rpm for 30 seconds, and then dry the film-forming solution spin-coated on the glass substrate at 60° C. for 20 minutes to obtain a silk fibroin composite film mx2.

[0066] Experimental Example 1

[0067] The samples prepared in Example 1 and Comparative Example 1 were sent to a Fourier transform infrared spectrometer for detection, and the results were Figure 2 In the FT-IR spectra, the upper solid line depicts the FT-IR spectrum of the silk fibroin composite film prepared by Example 1, and the lower dotted line depicts the FT-IR spectrum of the silk fibroin film prepared by Comparative Example 1.

[0068] from Figure 2It can be observed that the introduction of glycine-chitosan solution has a significant effect on the structure of the silk fibroin composite film: the spectrum of the silk fibroin film (Comparative Example 1) has peaks at 1550 and 1653 wavenumbers, which are typical peaks of α and random curl structures; while the spectrum of the silk fibroin composite film (Example 1) has peaks at 1232, 1548 and 1706 wavenumbers, which are typical peaks of β structure, indicating that the number of β structure in the silk fibroin composite film is significantly increased.

[0069] Experimental Example 2

[0070] Using a quasi-static piezoelectric constant measuring instrument, the longitudinal piezoelectric coefficient (d33) of each silk fibroin composite film obtained by Example 1 and the silk fibroin film samples prepared by Comparative Example 1 were tested at a scanning voltage of 0-10V. The test results are listed in the following Table 1.

[0071] Table 1 Longitudinal piezoelectric coefficients

[0072] Test samples m1 mx1 Piezoelectric coefficient (pc / n) 27 1

[0073] It can be observed from Table 1 above that the piezoelectric coefficient of the silk fibroin composite film m1 prepared by the preparation method of the present invention is significantly better than that of the pure silk fibroin film mx1 without glycine and chitosan, indicating that the β structure in the silk fibroin composite film is significantly improved by introducing glycine and chitosan, thereby significantly improving the longitudinal piezoelectric coefficient d33 of the silk fibroin composite film.

[0074] Experimental Example 3

[0075] Using an atomic force microscope, the Young's modulus of each silk fibroin composite film obtained in Example 1 and the samples of the silk fibroin film prepared in Comparative Example 2 were tested. The test results are listed in Table 2 below.

[0076] Table 2 Tensile strength

[0077] Test samples m1 mx2 Young's modulus(GPa) 2 5

[0078] It can be observed from Table 2 above that the mechanical strength of the silk fibroin composite film m1 prepared by the preparation method of the present invention is significantly better than that of the pure silk fibroin composite film mx2 without calcium chloride.

[0079] Based on the above experimental results, it can be explained that the preparation method of the present invention induces the crystallization of silk fibroin in the direction of β structure by introducing glycine-chitosan solution, overcomes the negative effect of calcium chloride on the number of β structures, and as a result, the β structure in the prepared silk fibroin composite film is significantly improved, so that the longitudinal piezoelectric coefficient is also significantly improved. At the same time, since the present invention retains the use of calcium chloride at the same time, the mechanical strength of the prepared silk fibroin composite film is guaranteed. Thus, the piezoelectricity and mechanical strength of the silk fibroin composite film are taken into consideration.

[0080] In addition, the preparation method of the present invention does not involve alcohol solution immersion, stretching and repolarization processing, is simple and efficient, and is conducive to large-scale production.

[0081] Although the numerical ranges and parameters advocated by the present invention are approximate values, the numerical values ​​described in the specific examples are as accurate as possible. However, any numerical value essentially has some errors that are inevitably caused in individual measurements. In the present invention, "about" generally refers to within 10%, 5%, 3%, 1%, 0.5% or 0.1% of a given value or range, or refers to within an average standard deviation acceptable to those skilled in the art. Outside the specific embodiments, unless otherwise specified, all numerical ranges, quantities, values ​​and ratios of the present invention, such as the amount of material, duration, temperature, operating conditions, the ratio of quantity, etc. should be understood to be modified by the word "about". In the present invention, the range can be expressed as from one endpoint to another endpoint, or between two endpoints. Unless otherwise specified, all ranges of the present invention include endpoints.

[0082] It can be understood that those skilled in the art can combine the features mentioned in one or more embodiments mentioned in the full text of the present invention with the features of other embodiments in any appropriate manner to implement the present invention.

[0083] Note that the above are only exemplary embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may also include more other equivalent embodiments without departing from the technical concept of the present invention, all of which belong to the protection scope of the present invention.

Claims

1. A method for preparing a silk fibroin composite piezoelectric film, characterized in that: The following steps are involved: Dissolving glycine powder in a chitosan acetic acid solution to obtain a glycine-chitosan composite solution, wherein the mass fraction of chitosan in the chitosan acetic acid solution is 1.5%, and the mass ratio of glycine to chitosan in the glycine-chitosan composite solution is 0.01 to 5:1; Dissolving silk fibroin powder in a formic acid-calcium chloride solution to obtain a silk fibroin solution with a silk fibroin mass fraction of 10%; The glycine-chitosan composite solution and the silk fibroin solution are uniformly mixed at a mass ratio of 0.1 to 0.5:1 to obtain a membrane-forming solution; The film-forming solution is spin-coated on a substrate, and the film-forming solution spin-coated on the substrate is dried to obtain a silk fibroin composite film.

2. The preparation method according to claim 1, characterized in that: The chitosan acetic acid solution is prepared by dissolving chitosan powder in 1 v / v % acetic acid solution.

3. The preparation method according to claim 1, characterized in that: After dissolving the glycine powder in the chitosan acetic acid solution, the method further includes vigorously stirring the glycine-chitosan composite solution at room temperature for more than 0.5 hour.

4. The preparation method according to claim 1, characterized in that: The mass ratio of glycine to chitosan in the glycine-chitosan composite solution is 0.8:

1.

5. The preparation method according to claim 1, characterized in that: The mass fraction of formic acid in the formic acid-calcium chloride solution is 70-99%, and the mass fraction of calcium chloride is 1-30%.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the glycine-chitosan composite solution to the silk fibroin solution is 0.2:

1.

7. The preparation method according to claim 1, characterized in that: The material of the substrate is selected from glass or polyethylene terephthalate.

8. The preparation method according to claim 1, characterized in that: The rotation speed of the spin coating is 1 to 1000 rpm, and the duration of the spin coating is less than 2000 seconds.

9. The preparation method according to claim 1, characterized in that: The drying temperature is 25 to 60° C., and the drying duration is less than 60 minutes.

10. A silk fibroin composite piezoelectric film, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silk fibroin composite film as well as preparation method and application thereof

    CN109722039A